2022
DOI: 10.1121/10.0013890
|View full text |Cite
|
Sign up to set email alerts
|

Strategic perceptual weighting of acoustic cues for word stress in listeners with cochlear implants, acoustic hearing, or simulated bimodal hearing

Abstract: Perception of word stress is an important aspect of recognizing speech, guiding the listener toward candidate words based on the perceived stress pattern. Cochlear implant (CI) signal processing is likely to disrupt some of the available cues for word stress, particularly vowel quality and pitch contour changes. In this study, we used a cue weighting paradigm to investigate differences in stress cue weighting patterns between participants listening with CIs and those with normal hearing (NH). We found that par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…As such, it is possible that listeners anticipated ambiguous speech input in the presence of the face mask and adjusted phonetic categories accordingly. Indeed, previous research has shown that when high frequency cues are dampened in the speech signal, listeners may upweight low frequency speech cues, which may be an adaptive weighting strategy implemented with mask use to improve speech perception, similar to acoustic cue weighting strategies observed in listeners with hearing loss (e.g., Crinnion et al, 2020 ; Fleming & Winn, 2022 ; Toscano & McMurray, 2010 ).…”
Section: Discussionmentioning
confidence: 94%
“…As such, it is possible that listeners anticipated ambiguous speech input in the presence of the face mask and adjusted phonetic categories accordingly. Indeed, previous research has shown that when high frequency cues are dampened in the speech signal, listeners may upweight low frequency speech cues, which may be an adaptive weighting strategy implemented with mask use to improve speech perception, similar to acoustic cue weighting strategies observed in listeners with hearing loss (e.g., Crinnion et al, 2020 ; Fleming & Winn, 2022 ; Toscano & McMurray, 2010 ).…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, previous research has shown that when high frequency cues are dampened in the speech signal, listeners may upweight low frequency speech cues, which may be an adaptive weighting strategy implemented with mask use to improve speech perception, similar to acoustic cue weighting strategies observed in listeners with hearing loss (e.g., Toscano & McMurray, 2010;Crinnion et al, 2020;Fleming & Winn, 2022).…”
Section: Perceptual Weighting Of Different External Cuesmentioning
confidence: 98%
“…First, each stimulus was presented five times. Repetition helps to identify speech perception patterns, which is often employed in studies to explore how acoustic cues affect word and sentence comprehension (e.g., Fleming & Winn, 2022; Holzgrefe-Lang et al, 2016; Petrone et al, 2017). However, this approach might lead to priming, learning, and habituation effects in listeners’ use of acoustic cues.…”
Section: Limitationsmentioning
confidence: 99%